PENGARUH MODEL ROTATING TRIO EXCHANGE (RTE) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SEMESTER GENAP SMP NEGERI 17 BANDAR LAMPUNG TAHUN PELAJARAN 2014/2015 - Noviyana, Hesti (LPPM STKIP PGRI Bandar Lampung, 2016)
This study aims to determine the effect of the Rotating Trio Exchange model on learning achievements of Mathematics subject of the eighth grade students of SMPN 17 Bandar Lampung in academic year 2014/2015 with the issues examined in the form of low Mathematics score of eighth grade students. This study used an experimental method which was conducting direct application usage models Rotating Trio Exchange (RTE) in the experimental class and conventional model in the control class. The population in this study is the second semester of eighth grade students of SMP Negeri 17 Bandar Lampung in academic year 2014/2015 with a sample of 2 classes taken by using cluster random sampling technique. The data was measured using essay test consisted 10 questions. The research instruments used by the writer must meet the criteria of a good instrument so the authors examined the instrument that researchers prepared in 32 respondents out of sample group. Based on the the result of the research, it is obtained that the results of tcount= 2.64 at distribution level 5% ttable= 2.02. It is proven that tcount> ttable so it can be concluded that there is the influence of the Rotating Trio Exchange (RTE) model towards the Mathematics learning achievements at the second semester of eighth grade students of SMPN 17 Bandar Lampung in academic year 2014/2015.